Resistance To Change: A Study On Sharia Bank Post-Merger And Its Correlation With Perceived Organizational Support - Mualif, Dhawy Ammar; Aprilia, Eka Dian; Mirza, Mirza; Riamanda, Irin (Program Studi Psikologi, Fakultas Kedokteran, Universitas Syiah Kuala, 2025)
X Bank is the largest sharia bank in Indonesia that was established as a merger between three state-owned sharia banks. This merger presents its own challenges with different characteristics of each bank and causing employees to adapt with the changes that occur in X Bank. These changes also play a role in the emergence of resistance to change. During organizational change, organizational support is one of the important parts that can help employees undergoing changes that occur within the organization.This study aims to examine the relationship between perceived organizational support and resistance to change on sharia bank employees post-merger.This research involved 194 samples using non-probability accidental sampling techniques. Data collection in this research is conducted using the Survey of Perceived Organizational Support (SPOS) and Resistance to Change Scale (RTCS) instruments and analyzed using Jeffreys Amazing Statistics Program (JASP). Results show that there is a negative relationship between perceived organizational support and resistance to change among X Bank employees in Banda Aceh. Results also found that perceived organizational support level for X Bank employees were averaging in the high category with resistance to change level for X Bank employees were averaging in the low category.